Correlação entre concentração liquórica e efeitos colaterais após injeção de morfina por via subaracnóidea em ratos - Silva, Neuzimar De Souza Freire [UNIFESP] (2004)
BACKGROUND AND OBJECTIVES: Spinal morphine promotes good pain relief, but is not free from side effects. This study aimed at verifying the correlation between CSF morphine concentration and side effects. METHODS: This study involved 4 groups of 7 rats, which were studied 24 hours after spinal catheter insertion via cisterna magna. Groups G1, G2, G3 and G4 received respectively 0.1; 0.3; 0.5 and 1 µg morphine in 10 µl of 0.9% saline solution. CSF samples were collected and side effects were recorded at M15, M30, M60, M120 and M180 minutes after injection. RESULTS: Side effects observed were: mandible tremors, agitation, pruritus, absence of diuresis, sedation, and respiratory changes. The incidence of side effects was higher during early evaluations and progressively decreased with time. Mean CSF morphine concentrations in G1 varied from 72.84 to 1.13 pg; in G2 from 114.26 to 5.68 pg; in G3 from 151.18 to 13.62 pg and in G4, from 561.37 to 18.61 pg. CONCLUSIONS: There has been no correlation between CSF morphine concentration and side effects.